Redesigning TRA concept to assess millennials’ intention to use public transportation services in Indonesia - Herdy Jaya Prawiradipura; Nicholas Wilson (Universitas Tarumanagara, 2023)
This study attempts to re-design the original concept of the theory of reasoned action (TRA) in order to explain millennials’ intention to use public transportation services in Indonesia. Using quantitative-survey method, a total of 137 respondents participated in this study. Respondents are millennials living in Indonesia who had used public transportation services (trains, buses, or MRT) regularly over the past 6 months. Using PLS, authors concluded that all three antecedents, namely attitude, perceived service affordability and subjective norms significantly influence millennials’ intention to use public transportation services in Indonesia. Penelitian ini mencoba untuk mengembangkan konsep dasar dari theory of reasoned action (TRA) guna menjelaskan keinginan dari para generasi milenial di dalam menggunakan jasa transportasi umum yang tersedia di Indonesia. Menggunakan metode survei-kuantitatif, sebanyak 137 responden berpartisipasi pada penelitian ini. Adapun para responden merupakan individu yang telah menggunakan jasa transportasi umum di Indonesia (baik bus, kereta ataupun MRT) secara berkala dalam kurun waktu 6 bulan terakhir. Dengan menggunakan metode PLS, peneliti menyimpulkan bahwa ketiga faktor, yaitu attitude, perceived service affordability, dan subjective norms, secara signifikan memengaruhi intensi para kaum milenial di dalam menggunakan jasa transportasi umum di Indonesia.